Racial/ethnic disparities in timing of death during childhood among children with congenital heart defects. Issue 10 (18th October 2013) - Nembhard, Wendy N.; Xu, Ping; Ethen, Mary K.; Fixler, David E.; Salemi, Jason L.; Canfield, Mark A.
<x xml:space="preserve">Abstract</x> BACKGROUND Infants with congenital heart defects (CHD) have increased risk of morbidity and mortality. Little is known about racial/ethnic differences in timing of death during childhood. Our intent was to investigate racial/ethnic differences in mortality for CHDs during specific time periods in childhood. METHODS Texas Birth Defect Registry data were used for a retrospective cohort study with 30, 015 singleton infants with a CHD, born January 1, 1999, to December 31, 2007, to non‐Hispanic (NH) white, NH‐black, or Hispanic women. Texas Birth Defect Registry data were linked to Texas death records to ascertain death. Kaplan–Meier survival probabilities and multivariable Cox‐proportional hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated. RESULTS NH‐blacks and Hispanics with specific CHDs had increased mortality during the postneonatal period and early childhood. NH‐blacks had increased postneonatal mortality compared with NH‐whites for transposition of the great arteries (HR = 2.4; 95% CI, 1.5–4.0), pulmonary valve atresia without ventricular septal defect (HR = 4.1; 95% CI, 1.7–9.7), Ebstein's anomaly (HR = 8.6; 95 CI, 1.2–61.1), hypoplastic left heart syndrome (HR = 2.1; 95% CI, 1.2–3.7), coarctation of the aorta (HR = 2.1; 95% CI, 1.2–3.5), ventricular septal defect (HR = 2.1; 95% CI, 1.6−2.8), and atrial septal defect (HR = 1.4; 95% CI, 1.1−1.8). Hispanics had increased postneonatal mortality risk for tetralogy of Fallot (HR = 2.0; 95% CI, 1.1–3.5). Racial/ethnic increases in mortality risk were also observed during infancy and childhood. CONCLUSION Racial/ethnic differences in mortality were most notably observed during the postneonatal period and early childhood. Future studies should assess factors associated with this disparity in mortality risk for infants with CHDs. Birth Defects Research (Part A) 97:628–640, 2013. © 2013 Wiley Periodicals, Inc.